The Effect of Calcium Source on Pb and Cu Remediation Using Enzyme-Induced Carbonate Precipitation - Wang, Lin; Cheng, Wen-Chieh; Xue, Zhong-Fei (Frontiers in Bioengineering and Biotechnology, 2022)
Heavy metal contamination can not only cause threats to human health but also raise sustainable development concerns. The use of traditional methods to remediate heavy metal contamination is, however, time-consuming, and the remediation efficiency may not meet the requirements as expected. The present study conducted a series of test tube experiments to investigate the effect of calcium source on the lead and copper removals. In addition to the test tube experiments, numerical simulations were performed using the Visual MINTEQ software package considering different degrees of urea hydrolysis derived from the experiments. The remediation efficiency degrades when NH4+ and OH- concentrations are not sufficient to precipitate the majority of Pb2+ and Cu2+. It also degrades when CaO turns pH into highly alkaline conditions. The numerical simulations do not take the dissolution of precipitation into account, and therefore, overestimate the remediation efficiency when subjected to lower Pb(NO3)2 or Cu(NO3)2 concentrations. The findings highlight the potential of applying the enzyme-induced carbonate precipitation to lead and copper remediations.